PTU-141 Circulating biomarkers for predicting the response to neoadjuvant therapy in oesophago-gastric cancer. (22nd June 2015) - Bunting, D; Sanders, G
Abstract : Introduction: Neoadjuvant therapy is used to improve survival in OG cancer, however, only 1 in 4 patients respond sufficiently to gain any benefit. Non-responders are exposed to the toxic effects of therapy and a delay to surgery. Predicting the response to neoadjuvant therapy could lead to more individualised patient care and better outcomes. Pre-therapy biomarkers have shown the most promise. Serum/plasma markers are not reliant on invasive tests, are repeatable and can often be measured using basic, widely available laboratory techniques. Method: A systematic search of the MEDLINE, Embase, and Cinharl databases was performed combining the terms "(o)esophageal cancer" or "gastric cancer" and "therapy", "chemotherapy" or "chemoradiotherapy" and "predict" and "response". Additional studies were identified through reference lists, and the PubMed search/related articles features. Only clinical studies and those using neoadjuvant therapies were included. Results: 542 articles were identified from the search, of which 28 met all criteria for inclusion in the analysis. Pre-therapy biomarkers predictive of response are presented in the table divided into groups according to marker function/pathway involved. The relationship between marker levels and outcome are detailed along with P- value, study size and author/publication year. Conclusion: A number of circulating biomarkers show potential for predicting response to neoadjuvant therapy and serial measurements may be able to monitor response in vivo . These markers need to be validated in larger, prospective studies before being adopted into randomised studies designed to investigate their potential clinical benefit. Disclosure of interest: None Declared.